"Go West, Young Woman?": The Geography of the Gender Wage Gap through the Great Recession. (8th August 2018) - Goodwin-White, Jamie
Abstract: Despite headline-grabbing accounts of the mancession and childless metropolitan-dwelling women who earn more than men, the gender wage gap remains persistent. However, the spatiality of the gender wage gap has received little attention. I ask whether, where, and how the gender wage gap changed with the Great Recession. Using American Community Survey pooled surveys for 2005–2007 and 2011–2013, I model counterfactual wage distributions for full-time male and female workers in the top one hundred metro areas of the United States, controlling for education, age, experience, and occupation. Gender inequality is polarizing spatially and across the wage distribution, and the recession exacerbates this pattern. Gender gaps decline most in the Rustbelt, but show relative increases in many Western metro areas. Further, declines are mostly among below-median earning workers, whereas increases are likely at the seventy-fifth or ninetieth percentiles. Disproportionate returns to men's characteristics explain much of these geographic and distributional shifts. The combination of geographic and distributional analysis reveals a more thorough picture of how gender inequality shifted with the recession, since previous patterns of uneven development under economic restructuring are still evident. The analysis also signposts regions of emerging gender inequality where relative equality is often presumed, suggesting critical research directions for feminist and economic geographers.